Ethics as a Transformational Strength in Education: An Ethical Leadership Perspective - Bipin Sherchan; Prateet Baskota; Mohan Singh Saud (Advanced Qualitative Research, 2024)
Ethical intelligence is the strength of a transformational society. As a change agent, the school leader is expected to be a representative figure of ethical standards. Unfortunately, they are criticized for their unethical activities. Therefore, drawing on the concept of ethical leadership, this study aims to construct the meaning of ethics as they have lived with it, thereby exploring the transformational influences of ethical strengths. Adopting a narrative inquiry research design, lived narratives were generated from four principals of secondary level (Grades 9-12) selected purposively. The narrative data were analyzed and interpreted using Starratt’s (2004) theoretical framework of ethical leadership of care, justice, and critique. This study explored ethics as the mutual value of individual, institutional, and social institutions. Human potentiality is the power of ethical intelligence that derives toward transformation. This finding sheds light on the importance and execution of ethical abilities. It shares ethical knowledge, values, and skills among individuals, schools, and communities. It also portrays ethical sensitivities, which are the core foundation of a transformative society with rational personalities.